2019
DOI: 10.1016/j.wnsx.2019.100025
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risks and Limited Indications of the Supraorbital Keyhole Approach for Clipping Internal Carotid Artery Aneurysms

Abstract: Background Internal carotid artery (ICA) aneurysm may be a good target for supraorbital keyhole clipping. We discuss the surgical indications and risks of keyhole clipping for ICA aneurysms based on long-term clinical and radiologic results. Methods This was a retrospective analysis of 51 patients (aged 35–75 years, mean 62 years) with ICA aneurysms (mean 5.8 ± 1.8 mm) who underwent clipping via the supraorbital keyhole approach between 2005 and 2017. Neurologic and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Recently, SOK was introduced as an alternative approach for clipping ICA aneurysms,[ 15 ] due to an increase in the demand for a shorter operation time and a less invasive method for achieving a better effect without complications,[ 4 ] However, reports about surgical treatment of PcA through this approach are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SOK was introduced as an alternative approach for clipping ICA aneurysms,[ 15 ] due to an increase in the demand for a shorter operation time and a less invasive method for achieving a better effect without complications,[ 4 ] However, reports about surgical treatment of PcA through this approach are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The SOK is not generally indicated to clip PcA, as suggested by Toyooka et al ., who performed keyhole clipping in only two PcAs (3.7%) among the 54 PcAs, which were very small in size and required partial anterior clinoidectomy;[ 15 ] yet, this limitation of SOK is explained by SOK that has a straight-axis trajectory, so limited operative angle hinders multidirectional observation and the manipulation of the target aneurysm. Therefore, in our opinion, the indication can be influenced by a sum of three criteria related to the aneurysm, including its dome size, direction, and neck sites.…”
Section: Discussionmentioning
confidence: 99%
“…Tang Y et al [ 43 ], Yu LB et al [ 51 ] and Chen L et al [ 7 ] reported 93.6%, 97.87% and 92% occlusion rate respectively for the treatment of ruptured anterior circulation aneurysm via SOKA. Toyooka T et al [ 45 ] found 100% occlusion rate for unruptured ICA aneurysm via SOKA.…”
Section: Discussionmentioning
confidence: 99%
“…Timely detection and treatment of intracranial aneurysms are crucial in prevention of rupture of intracranial aneurysms and subarachnoid hemorrhage 2 . Detection and precise morphologic evaluation of the aneurysm neck is important for intracranial aneurysm management and for the choice of treatment method [3][4][5] . Digital subtraction angiography (DSA) is the gold standard method in the diagnosis of preoperative intracranial aneurysms because of excellent depiction of cerebrovascular anatomy structures and superior spatial resolution in comparison with three-dimensional (3D)-computed tomography (CT) and magnetic resonance angiography (MRA) 6,7 .…”
Section: Introductionmentioning
confidence: 99%